Analysis and Design of Web-Based Management Information Systems for Culinary MSMEs in Cilegon - Tika Kristianti; Sayid Bahri Sriwijaya (Universitas Muhammadiyah Palu, 2025)
This research aims to analyze and design a web-based management information system for culinary MSMEs in Cilegon to improve operational efficiency and the quality of business decision-making. Using the Design Science Research (DSR) approach, this research identifies the functional needs of businesses through interviews, observations, and questionnaires, which are then used as the basis for system design. The developed system includes key features such as stock management, transaction recording, and automatic financial report generation. The trial results showed an increase in work time efficiency of up to 68%, a reduction in recording errors, and an increase in user satisfaction with an average usability score of 85 out of 100. The system also proved easy to use, even by users with low levels of digital literacy. The evaluation shows that the system is able to answer the real needs of MSME actors and has the potential to be replicated in other business sectors. This research concludes that a web-based management information system is an effective strategic solution in encouraging the digital transformation of culinary MSMEs, and can be a model for sustainable technology implementation in other regions.